Evaluation method of low temperature crack resistance of asphalt mixture based on equivalent fracture temperature
By introducing equivalent fracture temperature indexes in the evaluation of low-temperature crack resistance of asphalt mixture, the problem of breaking energy in the prior art is solved, and a higher degree of distinction and evaluation accuracy is achieved.
Patent Information
- Application Number
- CN202210172924.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-02-24
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2042-02-24
AI Technical Summary
In the existing low-temperature crack resistance evaluation method of asphalt mixture, fracture energy is insensitive to the RAP dosage in the regenerated asphalt mixture, making it difficult to effectively distinguish the low-temperature crack resistance of different asphalt mixtures.
The evaluation method based on equivalent fracture temperature was used to measure the fracture energy and flexural modulus through the trabecular bending test, and combined with the temperature shrinkage coefficient, the equivalent fracture temperature was calculated to evaluate the low-temperature crack resistance of the asphalt mixture.
The difference between low-temperature crack resistance of asphalt mixture is improved, and the low-temperature crack resistance of asphalt mixtures with different RAP dosage, asphalt grade and regenerator dosage is more effectively distinguished.
Smart Images

Figure CN114636622B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of application of asphalt mixture road performance evaluation, and specifically relates to an evaluation method for low-temperature crack resistance of asphalt mixture. Background Art
[0002] Low-temperature cracking is one of the main diseases of asphalt pavements. In order to reduce low-temperature cracking of asphalt pavements in seasonally frozen areas, it is necessary to select asphalt mixtures with excellent low-temperature crack resistance during asphalt pavement construction. Therefore, the test method and evaluation index of low-temperature crack resistance of asphalt mixtures are particularly important. The ideal low-temperature crack resistance test method should be simple to operate and easy to prepare specimens; the ideal low-temperature crack resistance evaluation index should be able to accurately evaluate the crack resistance of asphalt mixtures at low temperatures. At the same time, different asphalt mixtures should have large numerical differences, which can effectively distinguish the low-temperature crack resistance of different asphalt mixtures, and facilitate the selection of asphalt mixtures during pavement design.
[0003] At present, many evaluation indicators for the low-temperature crack resistance of asphalt mixtures have been proposed at home and abroad, such as fracture energy, strain energy density, low-temperature bending strain, creep rate, freezing fracture temperature, etc. Among them, fracture energy is the most widely used, because the fracture energy test method is simple and easy to operate, and the source of specimens is the largest, such as semicircular bending test, compact tensile test, beam bending test and indirect tensile test. It is generally believed that the larger the fracture energy, the more energy the asphalt mixture needs to consume when it breaks at low temperature, and the better the low-temperature crack resistance.
[0004] Fracture energy is a parameter that combines strength and strain, but it is difficult to distinguish between brittle materials with high strength and low ductility and flexible materials with low strength and high ductility. Compared with ordinary asphalt mixture, recycled asphalt mixture is a material with high strength and poor ductility, so the difference in fracture energy between ordinary asphalt mixture and recycled asphalt mixture is small. As a result, the fracture energy is not very sensitive to the RAP (reclaimed asphalt pavement) content in the recycled asphalt mixture. The difference in fracture energy of recycled asphalt mixtures with different RAP contents is small, and it is difficult to effectively distinguish their low-temperature crack resistance. Therefore, if a new evaluation index that can effectively distinguish the low-temperature crack resistance of recycled asphalt mixtures with different RAP contents can be proposed based on fracture energy, it will be of great significance to the promotion and use of recycled asphalt mixtures. Summary of the invention
[0005] The evaluation index fracture energy in the existing asphalt mixture low temperature performance evaluation method is not sensitive to the RAP content in the recycled asphalt mixture, and it is difficult to effectively distinguish the low temperature crack resistance of the recycled asphalt mixture. The present invention provides a method based on the newly proposed equivalent fracture temperature to improve the differentiation of the low temperature crack resistance of the mixture.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for evaluating the low-temperature crack resistance of asphalt mixture based on equivalent fracture temperature, the method comprising the following steps:
[0008] Step 1: Conduct a bending test on a small asphalt mixture beam; apply a concentrated load to the middle section of the beam top, record the load and mid-span deflection until the beam breaks in half, and obtain a load-mid-span deflection curve. Based on this curve, calculate the fracture energy and bending modulus of the asphalt mixture. x represents displacement, F(x) represents load, A represents fracture area, i.e. cross-sectional area; bending modulus R B is the flexural tensile strength of the specimen when it fails in the bending test (MPa), ε B is the maximum bending tensile strain when the specimen fails in the bending test (με);
[0009] Step 2: Determine the thermal shrinkage coefficient of asphalt mixture, and conduct the test according to the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20-2011) of my country; if the test conditions are not met, the formula can be used Estimate the thermal shrinkage coefficient of asphalt mixture, where VMA represents the void ratio of mineral aggregate, which is measured by the density test of asphalt mixture; V ag Represents the volume fraction of aggregate, which is calculated based on the gradation of asphalt mixture; α as It represents the thermal shrinkage coefficient of asphalt, which can be taken as 3.45×10 -4 (1 / ℃); α ag Indicates the thermal shrinkage coefficient of aggregate. According to the measurement results, the value of limestone is 5.1×10 -6 (1 / ℃), basalt takes 6.62×10 -6 (1 / ℃), granite takes 11.3×10 -6 (1 / ℃);
[0010] Step 3: According to the fracture energy, bending modulus and thermal shrinkage coefficient of asphalt mixture, according to the formula Calculate the equivalent fracture temperature of asphalt mixture; α represents the thermal shrinkage coefficient of asphalt mixture; L is the span of the asphalt mixture beam specimen;
[0011] Step 4: Use the equivalent fracture temperature to evaluate the low-temperature performance of the asphalt mixture; the lower the equivalent fracture temperature of the asphalt mixture, the worse its low-temperature anti-cracking performance, thereby distinguishing the low-temperature anti-cracking performance of different asphalt mixtures.
[0012] As a further preferred solution, the calculation of the equivalent fracture temperature in step 3 is derived based on the fracture energy index in the existing asphalt mixture evaluation method;
[0013] In the freeze-break test, the work done by the temperature stress of the asphalt mixture under a unit temperature drop (or the energy stored in the asphalt mixture) is defined as the energy absorption rate, which is represented by the symbol f. T In the beam bending test, the work done by the asphalt mixture to produce a unit strain mechanical load (or the energy stored in the asphalt mixture) is defined as the energy absorption rate, which is represented by the symbol f. ε Represents. The structural parameter Y is defined as the fracture energy divided by the energy absorption rate. According to the different definitions of the energy absorption rate, the parameter Y has two meanings. When the energy absorption rate represents the energy absorbed by the asphalt mixture per unit temperature drop, Y represents the temperature drop of the asphalt mixture, as shown in formula (1); when the energy absorption rate represents the energy absorbed by the unit strain, Y represents the strain generated by the asphalt mixture under temperature stress, as shown in formula (2).
[0014]
[0015]
[0016] Where: G f represents fracture energy; f represents energy absorption rate.
[0017] In the freeze-break test, the temperature stress of the asphalt mixture is generated due to the inability to shrink freely. Assuming that there are specimens of the same mixture that can shrink freely and the thermal shrinkage strain is recorded, the energy stored in the asphalt mixture in the freeze-break test can be calculated separately by the two defined energy absorption rates, and the energy of the two calculation methods is equal, as shown in formula (3).
[0018]
[0019] Where: T0 represents the starting temperature; T1 represents the end temperature; α(T) represents the temperature shrinkage coefficient of asphalt mixture.
[0020] Energy absorption rate f T and f ε Taking the average value, equation (3) can be rewritten as:
[0021]
[0022] make
[0023]
[0024] Formula (5) is the average value of the temperature shrinkage coefficient of asphalt mixture with respect to temperature. Substituting formula (5) into formula (4), we can get:
[0025]
[0026] Formula (6) shows the relationship between the two different definitions of energy absorption rate. Substituting formula (6) into formula (1) and (2) yields Y T and Y ε The conversion relationship is shown in formula (7).
[0027]
[0028] From formula (6), we can know that the energy absorption rate f T and f ε They can be converted into each other, so it can also be considered that the test results of the freezing fracture test and the test results of the beam bending test, SCB test or DCT test can be converted into each other.
[0029] In the beam bending test, the average energy absorption rate of the specimen after failure is It can be expressed as:
[0030]
[0031] Where: x represents displacement; F(x) represents load; ε m represents the fracture strain; A represents the fracture area.
[0032] At low temperature, the relationship between stress, strain, load and displacement at the bottom of the beam specimen center is shown in equations (9) and (10):
[0033]
[0034]
[0035] Where: b is the width of the specimen; h is the height of the specimen; L is the span of the specimen.
[0036] Substituting equations (9) and (10) into equation (8), we can obtain equation (11):
[0037]
[0038] Assuming that the stress-strain relationship of the beam at low temperature is linear, equation (11) can be simplified to:
[0039]
[0040] Where: m is the breaking strength.
[0041] Substituting equation (12) into equation (2) yields equation (13)
[0042]
[0043] Substituting equation (13) into equation (7), we obtain equation (14).
[0044]
[0045] Formula (14) can express the conversion relationship between the beam bending test and the freezing fracture test. The parameter Y T It indicates the temperature drop that the specimen can withstand, and its value is positive. It represents the thermal shrinkage coefficient of asphalt mixture, which can be obtained by actual measurement or prediction method. Under the condition of continuous cooling (such as the test condition of freezing test), the temperature strain and temperature curve are close to a straight line. Therefore, if there is no test condition to test the thermal shrinkage coefficient of asphalt mixture, the thermal shrinkage coefficient can be regarded as a constant. The model for estimating the thermal shrinkage coefficient of asphalt mixture is shown in formula (15).
[0046]
[0047] Where: VMA represents the void ratio of the aggregate; V ag represents the volume fraction of aggregate; α as It represents the thermal shrinkage coefficient of asphalt, which can be taken as 3.45×10 -4 (1 / ℃); α ag Indicates the thermal shrinkage coefficient of aggregate. For limestone, it is 5.1×10 -6 (1 / ℃), granite takes 11.3×10 -6 (1 / ℃).
[0048] The freezing and breaking temperatures of different asphalt mixtures are slightly different. In order to increase the differentiation of freezing and breaking temperatures of different asphalt mixtures, T The equivalent fracture temperature index Y is obtained by multiplying the fracture strain by ET , as shown in formula (16).
[0049]
[0050] Where: M is the bending modulus of the specimen when it breaks.
[0051] The physical meaning of the equivalent fracture temperature is similar to the freezing fracture temperature in the freezing fracture test, and can be used to evaluate the low-temperature crack resistance of asphalt mixtures. The test method and operation are simpler using the small beam bending test. The expression formula of the equivalent fracture temperature is similar to the allowable strain value (FST) of the compact tensile test and the crack resistance index (CRI) of the semicircular bending test. It has a greater degree of differentiation than the fracture energy for asphalt mixtures with different RAP content, asphalt grade, and regeneration agent content, and has a smaller coefficient of variation.
[0052] As a further preferred solution, in step 1, the specimen size of the beam bending test is selected to be 250 mm×35 mm×30 mm, and its span is 200 mm.
[0053] As a further preferred embodiment, in step 1, the beam bending test is carried out at -10°C.
[0054] As a further preferred embodiment, in step 1, the loading rate of applying concentrated load to the middle section of the top of the beam in the small beam bending test is 50 mm / min.
[0055] The method for evaluating the low-temperature crack resistance of asphalt mixture based on equivalent fracture temperature provided by the present invention can improve the differentiation of the low-temperature crack resistance of asphalt mixture. The physical meaning of the equivalent fracture temperature is similar to the freeze-break temperature in the freeze-break test, and can be used to evaluate the low-temperature crack resistance of asphalt mixture. The test method and operation are simpler. The expression formula of the equivalent fracture temperature is similar to the allowable strain value (FST) of the compact tensile test and the crack resistance index (CRI) of the semicircular bending test. It has a greater degree of differentiation for asphalt mixtures with different RAP dosages, asphalt grades, and regeneration agent dosages than the fracture energy, and has a smaller coefficient of variation. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 This is a schematic diagram of the asphalt mixture beam bending test;
[0057] Figure 2 To calculate the fracture energy and bending modulus in the bending test of asphalt mixture;
[0058] Figure 3 The relative changes of different evaluation indicators are used for different asphalt mixtures. DETAILED DESCRIPTION
[0059] The idea of the method for evaluating the low-temperature crack resistance of asphalt mixture provided by the present invention is to first measure the fracture energy and bending modulus of the asphalt mixture through the asphalt mixture beam bending test, and then determine the thermal shrinkage coefficient of the asphalt mixture, or determine the gap ratio of the mineral materials in the asphalt mixture, and obtain the thermal shrinkage coefficient of the asphalt mixture through the asphalt mixture thermal shrinkage coefficient model, and then calculate the equivalent fracture temperature of the asphalt mixture through the fracture energy, bending modulus and thermal shrinkage coefficient of the asphalt mixture, and finally evaluate the low-temperature crack resistance of the asphalt mixture according to the equivalent fracture temperature.
[0060] The method for evaluating the low temperature crack resistance of asphalt mixture of the present invention specifically comprises the following steps:
[0061] 1. Beam bending test.
[0062] The beam bending test was carried out in accordance with my country's "Test Code for Asphalt and Asphalt Mixtures for Highway Engineering" (JTG E20-2011).
[0063] Specimen size: The test specimen is an asphalt concrete beam of 250mm×35mm×30mm with a span of 200mm. The wheel roller is used to form the rutting plate specimen, and the beam specimen is obtained by cutting.
[0064] Test instrument: UTM-25 produced by IPC can be used for loading, and the load and deflection are automatically collected by the instrument.
[0065] Test conditions: The test was carried out at -10°C and the loading rate was set to 50 mm / min.
[0066] Test steps:
[0067] (1) Set the test temperature and place the beam specimen in an insulation box for 4 hours;
[0068] (2) Place the beam specimen on the support, set the loading rate, start the test, and record the load and mid-span deflection until the beam breaks in half, ending the test;
[0069] (3) Based on the load-mid-span deflection curve, calculate the fracture energy and bending modulus of asphalt mixture. Flexural modulus
[0070] 2. Temperature shrinkage coefficient of asphalt mixture
[0071] The thermal shrinkage coefficient of asphalt mixture was determined with reference to my country's "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20-2011).
[0072] Specimen size: The test specimen is an asphalt concrete prism specimen of 200mm×20mm×20mm. The wheel roller is used to form the rutting plate specimen, and the specimen is obtained by cutting.
[0073] Test instruments: shrinkage meter, high and low temperature cycle constant temperature water bath, metal probe, thermometer, caliper, etc.
[0074] Test steps:
[0075] (1) Inject methanol aqueous solution as refrigerant into a constant temperature water tank, control the water tank temperature to the test start temperature (+10°C), move the specimen into the water tank and keep the temperature constant for 30 minutes;
[0076] (2) After the temperature is maintained, quickly remove the specimen from the water tank, read the micrometer reading L0 as the shrinkage zero point, and then return the specimen to the water tank. Cool down to the predetermined end temperature (-30℃), maintain the temperature for 30 minutes, and measure the final reading L e .
[0077] (3) Based on the contraction zero point L0 and the final reading L e Calculate the thermal shrinkage coefficient of asphalt mixture.
[0078] Alternatively, the bulk relative density of asphalt mixture and the synthetic bulk relative density of mineral aggregates in accordance with the Test Code for Asphalt and Asphalt Mixtures for Highway Engineering (JTG E20-2011) can be measured to calculate the mineral aggregate void ratio VMA of asphalt mixture, and the resultant is substituted into the asphalt mixture temperature shrinkage coefficient model—Formula (15) to obtain the temperature shrinkage coefficient of asphalt mixture.
[0079] 3. Calculate the equivalent fracture temperature
[0080] According to the fracture energy, bending modulus and thermal shrinkage coefficient obtained from the asphalt mixture beam bending test and density test, the equivalent fracture temperature of the asphalt mixture is calculated according to formula (16). The equivalent fracture temperature is used to evaluate the low-temperature crack resistance of the asphalt mixture.
[0081] 4. The low-temperature crack resistance of asphalt mixture is evaluated by using the equivalent fracture temperature. The lower the equivalent fracture temperature, the worse the low-temperature crack resistance, thereby distinguishing the low-temperature crack resistance of different asphalt mixtures.
[0082] According to the test results, the relative changes of different evaluation indicators are as follows: Figure 3 As shown in the figure, it can be seen that the relative change of fracture energy is the smallest, that is, the lowest discrimination; the absolute fracture temperature Y T The relative change is greater than the fracture energy, that is, the discrimination is greater than the fracture energy; from the absolute fracture temperature Y T Further development of the equivalent fracture temperature Y ET The relative change is the largest and the discrimination is also the largest, indicating that the equivalent fracture temperature Y ET The differentiation of low-temperature crack resistance of different asphalt mixtures has been successfully improved.
[0083] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for evaluating the low-temperature crack resistance of asphalt mixture based on equivalent fracture temperature, characterized in that: The method comprises the following steps: Step 1: Conduct a bending test on a small asphalt mixture beam; apply a concentrated load to the middle section of the beam top, record the load and mid-span deflection until the beam breaks in half, and obtain a load-mid-span deflection curve. Based on this curve, calculate the fracture energy and bending modulus of the asphalt mixture. x represents displacement, F(x) represents load, A represents fracture area, i.e. cross-sectional area; bending modulus R B is the flexural tensile strength of the specimen when it is destroyed in the bending test MPa, ε B is the maximum bending tensile strain με when the specimen fails in the bending test; Step 2: Determine the thermal shrinkage coefficient of asphalt mixture and conduct the test according to the test procedures; if the test conditions are not met, use the formula Estimate the thermal shrinkage coefficient of asphalt mixture, where VMA represents the void ratio of mineral aggregate, which is measured by the density test of asphalt mixture; V ag Represents the volume fraction of aggregate, which is calculated based on the gradation of asphalt mixture; α as It represents the thermal shrinkage coefficient of asphalt, which can be taken as 3.45×10 -4 , 1 / ℃; α ag Indicates the thermal shrinkage coefficient of aggregate. According to the measurement results, the value of limestone is 5.1×10 -6 , 1 / ℃, basalt takes 6.62×10 -6 , 1 / ℃, granite takes 11.3×10 -6 , 1 / ℃; Step 3: According to the fracture energy, bending modulus and thermal shrinkage coefficient of asphalt mixture, according to the formula Calculate the equivalent fracture temperature of asphalt mixture; α represents the thermal shrinkage coefficient of asphalt mixture; L is the span of the asphalt mixture beam specimen; Step 4: Use the equivalent fracture temperature to evaluate the low-temperature performance of the asphalt mixture; the lower the equivalent fracture temperature of the asphalt mixture, the worse its low-temperature anti-cracking performance, thereby distinguishing the low-temperature anti-cracking performance of different asphalt mixtures.
2. The method for evaluating the low-temperature crack resistance of asphalt mixture based on equivalent fracture temperature according to claim 1 is characterized in that: The calculation of the equivalent fracture temperature in step 3 is derived based on the fracture energy index in the existing asphalt mixture evaluation method; In the freeze-break test, the work done by the temperature stress of the asphalt mixture under a unit temperature drop is defined as the energy absorption rate, which is represented by the symbol f. T In the beam bending test, the work done by the asphalt mixture to produce a unit strain mechanical load is defined as the energy absorption rate, which is represented by the symbol f ε It indicates that the conversion relationship between the two different defined energy absorption rates is derived, which is related to the temperature shrinkage coefficient of the asphalt mixture, so the test results of the freezing fracture test and the test results of the beam bending test, SCB test or DCT test can be converted to each other; Define parameter Y as the fracture energy divided by the energy absorption rate. When the energy absorption rate f is used T Indicates the temperature drop of asphalt mixture ΔT. When the energy absorption rate f is used ε It represents the strain Δε of asphalt mixture under temperature stress, according to the average energy absorption rate of the specimen in the beam bending test. The equivalent fracture strain Y is obtained ε Then, the absolute fracture temperature Y is obtained based on the conversion relationship between the two different definitions of energy absorption rate. T ; In order to increase the differentiation of freezing temperatures of different asphalt mixtures, T The equivalent fracture temperature Y is obtained by multiplying the fracture strain by ET , 3. The method for evaluating the low-temperature crack resistance of asphalt mixture based on equivalent fracture temperature according to claim 1 is characterized in that: In step 1, the specimen size for the beam bending test is selected to be 250 mm × 35 mm × 30 mm, and its span is 200 mm.
4. The method for evaluating the low-temperature crack resistance of asphalt mixture based on equivalent fracture temperature according to claim 1, characterized in that: In step 1, the beam bending test was carried out at -10°C.
5. The method for evaluating the low-temperature crack resistance of asphalt mixture based on equivalent fracture temperature according to claim 1 is characterized in that: In step 1, the loading rate of applying concentrated load to the middle section of the top of the beam in the small beam bending test is 50 mm / min.
Citation Information
Patent Citations
Method for evaluating low-temperature crack-resisting performance of asphalt mixture
CN102109441A
Test equipment and method for analyzing low-temperature fracture performance of asphalt
CN108627402A
Cited By
Method for rapidly predicting freezing fracture temperature of mixture based on low-temperature mechanical properties of asphalt
CN121171402A